Eﬀects of the antibrotante cipc and the storage temperature of potatoes (Solanum tuberosum L.) - Jiménez Monroy, Luis A. (2018)
The objective of this research was to measure the effect of the antibrotating isopropyl-n (3-chlorophenyl) (CIPC) on Monte Bonito and Baronesa potato cultivars. The treatment was carried out by immersion in CIPC solution 0.5 and 1.0%, stored at 4.10 ° C and at room temperature. The quality of the tubers during storage was measured by the following parameters: weight loss, activity level of the enzyme polyphenol oxidase (PFO) and sprouting in different periods of storage. In general, the tubers of the cv, Baronesa were better preserved than those of the cv. Monte Bonito The only concentration of the CIPC that affected the quality of the tubers was 1.0%, which reduced the outbreak to 45 days and the weight loss up to 135 days of storage independent of temperature. On the other hand, treatment with CIPC concentration affected sugar levels.